COI Gene–Based Molecular Identification of Nineteen Butterfly Caterpillars (Order: Lepidoptera) of Bangladesh (Bangladesh Journal of Zoology, 2025)
The application of mitochondrial Cytochrome c oxidase subunit I (COI) gene-based molecular techniques for species identification and phylogenetic analysis offers distinct advantages when applied to butterfly caterpillars (larvae), compared to traditional methods reliant on adult morphology. In this study, we successfully amplified and sequenced an average of 626 base pairs of the COI gene from caterpillars representing nineteen different butterfly species. Sequence similarity searches using BLAST confirmed high matches with corresponding species entries in the GenBank database, validating the accuracy of our molecular identifications. All sequences were subsequently submitted to GenBank and assigned accession numbers. Phylogenetic analysis revealed two well-supported clades (Clade A and Clade B), with high bootstrap values (81–99), indicating distinct evolutionary lineages and a shared common ancestor among the species. Sequences clustered with conspecific data from other regions, reinforcing the reliability of COI-based phylogenetics. This study underscores the effectiveness of DNA barcoding as a non-invasive and accurate method for species identification across life stages, supporting advancements in taxonomy, biodiversity monitoring, and conservation biology, particularly when adult specimens are unavailable or lack distinguishing morphological features. Bangladesh J. Zool. 53(2): 149-157, 2025